Retrospective Orientations in Metropolitan Toronto and their Implications for Preservation and Presentation of the Historical Environment - Konrad, Victor; Taylor, S. (Urban History Review / Revue d'histoire urbaine, 1980)
Retrospective orientations of Toronto residents are indicated by dispositions toward general interest in the past, direct experience with survivals, appreciation of heritage, and conservation of historical remains. These dispositions indicate a strong, positive sentiment toward the past that is expressed by substantial involvement with the historical environment and highly uniform attitudes toward it. Torontonians care about their past. Implications for historical resource management are that they should be given additional opportunities to become involved with it, and that these opportunities should recognize the broad social base of concern and interest.